Mergers, Litigation and Efficiency - Oliver Gürtler; Matthias Kräkel (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
We consider antitrust enforcement within the adversarial model used by the United States. We show that, under the adversarial system, the Antitrust Authority may try to prohibit mergers also in those cases in which litigation is inefficient. Even if market concentration and technological disadvantages lead to a significant welfare reduction after merger, from society's perspective the agency's lawsuit may be inefficient. We can show that these inefficiencies may be aggravated if the takeover is hostile.
urn:nbn:de:bvb:19-epub-13366-2
Keywords: D43; K21; L40; 330; hostile takeover; litigation contest; merger